The Effect of Motivation on Pro Environmental Behavior (PEB) on Senior High School Student - Desi Eka Nur Fitriana; Mieke Miarsyah; Rusdi Rusdi (Universitas Negeri Jakarta, 2019)
ABSTRACT Proenvironmental behavior is a behavior that seeks to minimize the negative impact on the environment which is influenced by several factors, one of which is motivation. This study aims to analyze the direct effect of motivation on proenvironmental behavior. This research was conducted using a quantitative approach with a causal survey method and analyzed using path analysis. The number of samples used as respondents is 200 students of class XI MIA SMAN 1 Tangerang Regency. Based on the results of testing the hypothesis it can be concluded that there is a positive direct effect of personality on proenvironmental behavior with a path analysis coefficient of 0.159. There is a positive direct effect of motivation on proenvironmental behavior with a path coefficient of 0.486. Keywords: Motivation, Pro Environment Behavior, Path Analysis.